2018
DOI: 10.1111/apps.12178
|View full text |Cite
|
Sign up to set email alerts
|

Examining Cross‐Cultural Differences in Academic Faking in 41 Nations

Abstract: This study examines cross‐cultural differences in students’ academic faking (indicated by claiming to have impossible knowledge about mathematical concepts) by relating data from the Programme for International Student Assessment (PISA) to the comprehensive cultural framework of the Global Leadership and Organizational Behavior Effectiveness (GLOBE) project. Data of N = 233,428 students from 41 countries showed a substantial amount of variance in academic faking between cultures. Students’ academic faking was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Future research should include additional variables beyond economic predictors that were the focus of this study. In particular, previous research has suggested that cross‐country differences in faking correlates with three cultural dimensions of humane orientation, in‐group collectivism, and gender egalitarianism (Fell & König, 2016, 2020; Fell et al, 2016; see also Fell & König, 2020). Furthermore, future research should also study other kinds of ethically questionable behavior within the field of personnel selection (e.g., applicants unfairly using their influence and networks to get job interview invitations) and beyond and explore possible links to economic inequality.…”
Section: Discussionmentioning
confidence: 99%
“…Future research should include additional variables beyond economic predictors that were the focus of this study. In particular, previous research has suggested that cross‐country differences in faking correlates with three cultural dimensions of humane orientation, in‐group collectivism, and gender egalitarianism (Fell & König, 2016, 2020; Fell et al, 2016; see also Fell & König, 2020). Furthermore, future research should also study other kinds of ethically questionable behavior within the field of personnel selection (e.g., applicants unfairly using their influence and networks to get job interview invitations) and beyond and explore possible links to economic inequality.…”
Section: Discussionmentioning
confidence: 99%
“…When used in combination with personality inventories, overclaiming scores allow for filtering out error variance from personality scores that is due to faking (Bing et al , 2011). Cross-cultural differences in the extent of overclaiming do exist, as was found with an overclaiming test that asked respondents on their familiarity with nonexistent mathematical concepts (Fell and König, 2020; Fell et al , 2019; Vonkova et al , 2018). This is expected for overclaiming measures that do not take personal relevance of the tested knowledge domain into account.…”
Section: Literature Review and Hypothesesmentioning
confidence: 91%